Who Owns Haiti? : People, Power, and Sovereignty - Wilentz, Amy; Freeman, Scott (Lecturer); Maguire, Robert E. (Robert Earl), 1948- (Book collections on Project MUSE., 2017)
"Contributors illuminate the role of external actors in Haitian sovereign affairs over the course of the last decade, concurrently discussing how Haitians reinforce their self-determination on economic, political, and cultural levels"--Provided by publisher.